Public Policy Research—Born in the USA, at Home in the World? - Nils C. Bandelow; Nicole Herweg; Johanna Hornung; Reimut Zohlnhöfer (Politische Vierteljahresschrift, 2022)
Public policy emerged as an academic subfield in the United States after the second World War. The theoretical foundations of the discipline are essentially based on analyses of Anglo-Saxon policies and politics and were originally aimed at providing knowledge for the policy process of pluralistic democracies. Given the increasing transfer of the subject and related approaches to other countries, it is necessary to clarify how suitable theories, goals, and methods of policy research are applied in other contexts. What needs to be considered when transferring theories of the policy process, and what can be learned from existing applications of the various approaches in different settings? The compilation of contributions on selected theoretical public policy lenses and their transfer to other countries and regions provides a~nuanced answer to these questions. – – Policy-Forschung ist als wissenschaftliche Teildisziplin nach dem Zweiten Weltkrieg in den USA entstanden. Das theoretische Fundament des Fachs basiert wesentlich auf Analysen angelsächsischer Politik und war ursprünglich darauf ausgerichtet, Wissen für politische Prozesse in pluralistischen Demokratien bereitzustellen. Angesichts der zunehmenden internationalen Ausbreitung des Fachs ist zu klären, inwiefern die Theorien, Ziele und Methoden für Anwendungen in anderen politischen Systemen geeignet sind. Was muss jeweils bei einer Übertragung von Theorien der Policy-Forschung beachtet werden, und was lässt sich aus den bisherigen Anwendungen der verschiedenen Ansätze in unterschiedlichen Kontexten lernen? Die Zusammenstellung von Beiträgen zu ausgewählten Ansätzen und deren Transfer in andere Länder und Regionen gibt eine differenzierte Antwort auf diese Fragen.
Keywords: 320; Policy studies; Policy analysis; Theories of the policy process; Policy sciences; Comparative politics; Politikfeldanalyse; Staatstätigkeitsforschung; Theorien politischer Prozessforschung; Öffentliche Politik; Vergleichende Regierungslehre